PENGARUH FASILITAS, PENEMPATAN KERJA DAN KOMITMEN TERHADAP KINERJA PEGAWAI DINAS PANGAN DAN PERTANIAN KOTA TANJUNGBALAI - Erlinda Hayani; Suparna .; Fajar Oza Pratama; Sari Quratul Ainy; Erwin . (Manajemen dan Bisnis, 2021)
The formulation of the problem in this study are: How the effect of facilities, job placement and commitment to the performance of the employees at Dinas Pangan Dan Pertanian Kota Tanjungbalai. This study aims to determine the effect of facilities, job placement and commitment to employee performance. The sample in this study were 38 people. The results showed; Facility variable partially has a positive effect on employee performance; Job placement variables partially have a positive effect on employee performance; The commitment variable partially has a positive  effect on employee  performance;  Facility  variables,  work placement and  commitment   simultaneously   have  a  positive   and  significant   effect  on employee performance.